Atoll island states and international law : climate change displacement and sovereignty - Yamamoto, Lilian; Esteban, Miguel (Heidelberg : Springer, 2014)
Atoll Island States exist on top of what is perceived to be one of the planet's most vulnerable ecosystems: atolls. It has been predicted that an increase in the pace of sea level rise brought about by increasing greenhouse gas concentrations in the atmosphere will cause them to disappear, forcing their inhabitants to migrate.
Includes bibliographical references and index.
Keywords: Climatic changes -- Law and legislation; Climatic changes -- Political aspects; Coral reefs and islands